PENGARUH BIG FIVE PERSONALITY PADA KINERJA AUDITOR KANTOR AKUNTAN PUBLIK PROVINSI BALI - Pradnya Dewi, I Gusti Ayu Agung; Suardikha, I Made Sadha; Budiasih, I Gusti Ayu Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis, 2015)
This study aimed to determine whether personality dimensions in Big Five Personality model that consist of extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience will be able to influence auditor performance in public accounting firms in Bali. Previous studies have shown that personality dimensions in this model related to performance (Barrick dan Mount, 1991; Barrick dkk, 2001; Rothmann dan Coetzer, 2003). The data was collected using survey method with questionnaire. Samples that used in this study were 56 auditors and selected by purposive sampling method. The analysis technique used is multiple linear reggression. The result showed that only extraversion and agreeableness had positive effect on auditor performance, but conscientiousness, emotional stability, and openness to experience did not have any effect on auditor performance.
Keywords: auditor performance, big five personality, public accounting firms